Astragalus bartinense (Fabaceae), a new species from Turkey - Tunçkol, Bilge (Array, 2020)
Astragalus bartinense is described as a new species from Bartın Province in Northern Anatolia, Turkey. The new species is close to A. depressus L. and A. froedinii Murb., but distinctly differs from A. froedinii in having hairy fruit, long stipules (10–12 mm) and peduncle (10–25 mm). It also differs from A. depressus in having long stipules and a stipitate and glabrous ovary. Taxonomic descriptions, micromorphology of pollen and seed and geographical distribution are presented.